The Effects of Learning Strategies on Higher Order Thinking Skills - Kasmudin Mustapa (Pascasarjana UM, 2014)
Pengaruh Strategi Pembelajaran terhadap Kemampuan Berpikir Tingkat TinggiAbstract: The aim of this study to examine and explain interaction the difference among students’ higher order thinking skills taught using online learning and using expository with goal orientation of learning and goal orientation of performance on basic chemistry course. Using a quantitative ap-proach to quasi-experimental research design. The subjects were students of chemistry education, consisting of 57 students (experiment) and 55 students (control). The instrument research was a written test and questionnaires. The data were analyzed using Anova (Analysis of Variance). The research findings there are differences among students’ higher order thinking skills with a mean post-test online instructional strategies is 45.16 higher than students taught using expository instructional strategy which is 39.28, instructional goal orientation is higher 44.24 than 40.07 performance goal orientation. there is no interactions between online instructional strategies and expository with different goal orientation on students’ higher order thinking skills in basic chemistry courses. Key Words: online, expository, goal orientation, higher order thinking skills, basic chemistry Abstrak: Penelitian ini bertujuan untuk menguji dan menjelaskan interaksi, perbedaan kemampuan berpikir tingkat tinggi mahasiswa yang diberi perlakuan pembelajaran online dan ekspositori dengan orientasi tujuan belajar dan orientasi tujuan penampilan pada mata kuliah kimia dasar. Menggunakan pendekatan kuantitatif dengan rancangan eksperimen semu. Subjek penelitian adalah mahasiswa pendidikan kimia berjumlah 57 orang (eksperimen) dan 55 orang (kontrol). Instrumen penelitian adalah lembar tes tertulis dan angket. Data Penelitian ini dianalisis dengan teknik Anova. Hasil penelitian ditemukan; terdapat perbedaan kemampuan berpikir tingkat tinggi mahasiswa dengan rerata posttest yang diberi perlakuan strategi pembelajaran online 45,16 lebih tinggi dari strategi pembelajaran ekspositori 39,28; serta rerata orientasi tujuan belajar 44,24 lebih tinggi dari orientasi tujuan penampilan 40,07. Namun tidak terdapat interaksi antara pembelajaran online dan ekspositori dengan orientasi tujuan berbeda terhadap kemampuan berpikir tingkat tinggi mahasiswa pada mata kuliah kimia dasar.Kata kunci: online, ekspositori, orientasi tujuan, kemampuan berfikir tingkat tinggi, kimia dasar